A Global Survey of International Business Education in the 1990s - Kwok, Chuck C. Y.; Arpan, Jeffrey; Folks,, William R. (Journal of International Business Studies, 1994)
This article presents the major findings of the fifth global curriculum survey of the Academy of International Business (AIB)—an examination of the status and trends in international business education around the world as of the early 1990s. The survey's findings, based on responses from more than 500 business schools, encompass different goals and methods of internationalization, international linkages and experiential activities, organizational issues, amounts of internationalization progress achieved, and degrees of administrative satisfaction with progress achieved. The overall conclusion is that considerable progress has been made, but much more remains to be accomplished.